Length-length, length-weight relationship and condition factor of an ecological invader, Cyprinus carpio (Linneaus, 1758) from Manasbal Lake of Kashmir Himalaya, India - Andrabi, Saima; Parveen, Muni; Bakhtiyar, Yahya (Journal of Fisheries, 2021)
The common carp Cyprinus carpio is a well-known invasive species. A total of 472 specimens of C. carpio (8.6–35 cm, 10.5–1000 g) were collected from Manasbal Lake of Kashmir Himalaya for this study between March 2018 and February 2020. A strong correlation between the respective parameters of length-length and length-weight with r and R2 values approaching to 1 in both. The regression analysis indicated negative allometric growth for both sexes. For female, b value ranged from 2.04 (in spring) to 2.80 (in summer) whereas for male, it varied from 1.99 (in spring) to 2.99 (in summer). The value of Fulton’s (K) and relative (Kn) condition factors were greater than 1 in every season for both sexes which indicated that C. carpio population in the Manasbal Lake is in a good health condition and the water quality parameters along with other respective factors are favourable for successful thriving of this fish in the lake. The present study will be helpful to develop future strategies in terms of sustainable management of invasive C. carpio in the Manasbal Lake and similar water bodies.